Plasma AR Copy Number Changes and Outcome to Abiraterone and Enzalutamide - Gurioli, Giorgia; Conteduca, Vincenza; Lolli, Cristian; Schepisi, Giuseppe; Gargiulo, Stefania; Altavilla, Amelia; Casadei, Chiara; Scarpi, Emanuela; De Giorgi, Ugo (Frontiers in Oncology, 2020)
Introduction. Plasma androgen receptor (AR) copy number (CN) status identifies castration-resistant prostate cancer (CRPC) patients with worse outcome on abiraterone/enzalutamide. However, the impact of AR CN changes on clinical outcome in CRPC is unknown. Materials and Methods. Plasma samples from 73 patients treated with abiraterone or enzalutamide were collected at baseline and at the time of progression disease (PD). Droplet digital polymerase chain reaction was used to assess AR CN status. Results. We showed that 11 patients (15.1%) changed AR CN status from baseline to PD (9 patients from normal to gain, 2 from gain to normal). Patients changing AR CN status from normal at baseline to gain at PD had intermediate median overall survival (OS) of 20.5 months (95% CI 8.0-44.2) between those who remained AR CN normal from baseline to PD (27.3 months [95% CI 21.9-34.4]) and those who remained AR CN gain from baseline to PD (9.1 months [95% CI 3.8-14.5]) (p < 0.0001). Patients changing AR CN from normal at baseline to gain at PD had a median progression-free survival (PFS) of 9.2 months (95% CI 2.0-14.7), patients who remained AR CN normal had a median PFS of 9.1 months (95% CI 7.2-10.1) and patients who remained AR CN gain had a median PFS of 5.4 (95% CI 3.6-6.5) (p= 0.0005). Both OS and PFS were not significantly different between patients with AR CN that changes from normal to gain and patients with stable AR CN normal. Conclusions. We showed that CRPC patients changing AR CN status from baseline to progression time point had intermediate OS and we suggested that AR CN evaluation at baseline could be the most informative for clinical outcome of CRPC patients treated with abiraterone or enzalutamide. Larger prospective studies are warranted.